MiR-195 Inhibits Tumor Growth and Metastasis in Papillary Thyroid Carcinoma Cell Lines by Targeting CCND1 and FGF2. (27th June 2017) - Yin, Yali; Hong, Shubin; Yu, Shuang; Huang, Yanrui; Chen, Shuwei; Liu, Yujie; Zhang, Quan; Li, Yanbing; Xiao, Haipeng
Abstract : Background . MicroRNA (miRNA) dysregulation was commonly seen in papillary thyroid carcinoma (PTC), and miR-195 was verified to be downregulated in PTC by the large data set analysis from The Cancer Genome Atlas (TCGA). Our study aimed to explore the biological functions and the underlying molecular mechanisms of miR-195 in PTC. Methods . The relative expression of miR-195 and its target genes were assessed by quantitative RT-PCR assay in 38 pairs of PTC and the adjacent thyroid tissues. Assays were performed to evaluate the effect of miR-195 on the proliferation, migration, and invasion in PTC cell lines. Moreover, we searched for targets of miR-195 and explored the possible molecular pathway of miR-195 in PTC. Results . We found that miR-195 was downregulated in PTC cell lines and tissues. Overexpression of miR-195 significantly inhibited cell proliferation, migration, and invasion in K1 and BCPAP cell lines. CCND1 and FGF2, which had inverse correlations with miR-195 in clinical specimens, were found to be the direct targets of miR-195 . Furthermore, miR-195 might be involved in PTC tumorigenesis by suppressing the Wnt/ β -catenin signaling pathway. Conclusions . These results highlight an important role of miR-195 in the initiation and progression of PTC and implicate the potential application of miR-195 in PTC target therapy.